Comparative research of financial statements of Ukraine and China - Jinyang, Xu (Харківський національний автомобільно-дорожній університет, 2025)
The theoretical, methodological and practical aspects of the formation of financial reporting of an enterprise are studied: the essence and definition of financial reporting are clarified, its composition and types are outlined; the historical stages of the formation of financial reporting in Ukraine and China are studied, the legislative framework and principles of financial reporting are described; the methodology for preparing financial reporting in Ukraine and the stages of its preparation in Ukraine and China are outlined, a comparative analysis of the features of preparing financial reporting and the current charts of accounts in Ukraine and China is carried out.
Keywords: financial reporting; accounting; national regulations; international standards; management decisions; reporting